2011
DOI: 10.1007/978-3-642-23626-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Detection, Grading and Classification of Coronary Stenoses in Computed Tomography Angiography

Abstract: Abstract.Recently conducted clinical studies prove the utility of Coronary Computed Tomography Angiography (CCTA) as a viable alternative to invasive angiography for the detection of Coronary Artery Disease (CAD). This has lead to the development of several algorithms for automatic detection and grading of coronary stenoses. However, most of these methods focus on detecting calcified plaques only. A few methods that can also detect and grade non-calcified plaques require substantial user involvement. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…Dinesh et al 30 proposed a method that utilized manual centerlines and artery classification, and did not provide specific stenosis calculation and was evaluated with a small number of patients (eight patients). Recently, Kelm et al 32 and Goldenberg et al 33 also published automated detection of obstructive (≥50% stenosis) coronary artery lesions from CTA. A performance comparison between our proposed algorithm (both lesions with ≥50% stenosis and ≥25% stenosis) and these studies (lesions with ≥50% stenosis) is shown in Table 4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dinesh et al 30 proposed a method that utilized manual centerlines and artery classification, and did not provide specific stenosis calculation and was evaluated with a small number of patients (eight patients). Recently, Kelm et al 32 and Goldenberg et al 33 also published automated detection of obstructive (≥50% stenosis) coronary artery lesions from CTA. A performance comparison between our proposed algorithm (both lesions with ≥50% stenosis and ≥25% stenosis) and these studies (lesions with ≥50% stenosis) is shown in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] A few studies attempted automatic detection of coronary lesions. [29][30][31][32][33] Detection and quantification of coronary artery lesions are particularly challenging due to limited spatial resolution and coronary artery motion, relatively small plaque size, and complex and variable coronary artery anatomy. [29][30][31][32][33] Automated lesion detection requires accurate extraction of coronary artery centerlines and classification of normal and abnormal lumen cross-sections, quantification of luminal stenosis, and classification of lesions with different degree of stenosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dey and others [5] also used intravascular ultrasound (IVUS) to verify their method. Kelm and others [6] introduced a stenosis detecting system focusing on coronary CTA, which employed a nonlinear regression method to estimate the vessel diameter of a 2D vessel cross section to obtain the stenosis point of the vessel. Xu and others [7] presented a method for detecting and quantifying coronary arterial stenosis in CTA using the Fuzzy Distance Transform (FDT) approach and developed a method to estimate the "expected diameter" along a given arterial branch using a coherence analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Even in cases of severe coronary calcification, sensitivity and specificity of CTA in comparison to invasive angiography for significant stenosis are high [1]. Furthermore, automatic systems have been developed that enable the detection and grading of coronary stenoses based on accurate lumen estimations [2]. Recent studies also show that the blood pressure analysis of coronary arteries is a better predictor for ischemia-causing lesions than anatomically visible lumen obstructions.…”
Section: Introductionmentioning
confidence: 99%